Chronic miR‐29 antagonism promotes favorable plaque remodeling in atherosclerotic mice. Issue 6 (2nd May 2016) - Ulrich, Victoria; Rotllan, Noemi; Araldi, Elisa; Luciano, Amelia; Skroblin, Philipp; Abonnenc, Mélanie; Perrotta, Paola; Yin, Xiaoke; Bauer, Ashley; Leslie, Kristen L; Zhang, Pei; Aryal, Binod; et al.
Abstract: Abnormal remodeling of atherosclerotic plaques can lead to rupture, acute myocardial infarction, and death. Enhancement of plaque extracellular matrix (ECM) may improve plaque morphology and stabilize lesions. Here, we demonstrate that chronic administration of LNA‐miR‐29 into an atherosclerotic mouse model improves indices of plaque morphology. This occurs due to upregulation of miR‐29 target genes of the ECM (c ol1A and col3A ) resulting in reduced lesion size, enhanced fibrous cap thickness, and reduced necrotic zones. Sustained LNA‐miR‐29 treatment did not affect circulating lipids, blood chemistry, or ECM of solid organs including liver, lung, kidney, spleen, or heart. Collectively, these data support the idea that antagonizing miR‐29 may promote beneficial plaque remodeling as an independent approach to stabilize vulnerable atherosclerotic lesions. Synopsis: Antagonizing miR‐29 decreases atherosclerotic lesion size and improves indices of plaque stability. LNA‐miR‐29 treatment increases ECM components in the plaque compared to adjacent non‐plaque vessel, and treated VSMC secretome analysis indicates that ECM proteins are highly regulated by miR‐29. Antagonism of miR‐29 reduces atherosclerotic lesion size. Reducing miR‐29 improves indices of plaque stability. Manipulating miR‐29 in vitro influences the VSMC secretome. Abstract : Antagonizing miR‐29 decreases atherosclerotic lesion size and improves indices of plaque stability. LNA‐miR‐29 treatment increases ECM components in the plaque compared to adjacent non‐plaque vessel, and treated VSMC secretome analysis indicates that ECM proteins are highly regulated by miR‐29.